Nonwoven Production from Waste Rice Straw by Using Enzymatic Method. Issue 7 (2nd July 2020) - Agirgan, Mehtap; Taskin, Vedat
ABSTRACT: In this study, the nonwoven fabric is produced by rice straws to utilize agricultural organic waste. Rice straws dried after harvest are pretreated with NaOH, pectinase enzyme and wetting agent. Washed and softened fibers are cut at 4–5 cm staple length, blended in carding engine with cotton at 9/1 ratio. By carding band and needle punch process nonwoven fabric is obtained. SEM, EDX and FTIR analyses are applied on the fabric. Product's inspection verified that pretreatments provided smoothness, removed noncellulosic substances, and decreased hydrophobic structure. Thus, a new nonwoven material to be used in textile is produced.